Comparison of Metarhizium isolates for biocontrol of helicoverpa armigera (Lepidoptera : Noctuidae) in chickpea - Kulkarni, Shuklangi A.; Ghormade, Vandana; Kulkarni, Girish; Kapoor, Manisha; Chavan, Santosh B.; Rajendran, Armugam; Patil, Sanjay K.; Shouche, Yogesh; Deshpande, Mukund V. (Biocontrol Science and Technology, 2008)
Metarhizium isolates from soil (53) and insect hosts (10) were evaluated for extracellular production of cuticle degrading enzyme (CDE) activities such as chitinase, chitin deacetylase (CDA), chitosanase, protease and lipase. Regression analysis demonstrated the relation of CDE activities with Helicoverpa armigera mortality. On basis of this relation, ten isolates were selected for further evaluation. Subsequently, based on LT(50) of the 10 isolates towards H. armigera, five isolates were selected. Out of these five isolates, three were selected on the basis of higher conidia production (60-75 g/kg rice), faster sedimentation time (ST(50)) (2.3-2.65 h in 0.1% (w/v) Tween 80) and lower LC(50) (1.4- 5.7 x 10(3) conidia/mL) against H. armigera. Finally, three Metarhizium isolates were selected for the molecular fingerprinting using ITS sequencing and RAPD patterning. All three isolates, M34412, M34311 and M81123, showed comparable RAPD patterns with a 935G primer. These were further evaluated for their field performance against H. armigera in a chickpea crop. The percent efficacies with the three Metarhizium isolates were from 65 to 72%, which was comparable to the chemical insecticide, endosulfan (74%).
Keywords: appressorium formation; chitin deacetylase; chitinase; chitosanase; Helicoverpa armigera; Lipase; Metarhizium anisopliae; Protease

Chitin synthase inhibitors as antifungal agents - Chaudhary, Preeti M.; Tupe, Santosh G.; Deshpande, Mukund V. (Mini-Reviews in Medicinal Chemistry, 2013)
Increased risk of fungal diseases in immunocompromised patients, emerging fungal pathogens, limited repertoire of antifungal drugs and resistance development against the drugs demands for development of new and effective antifungal agents. With greater knowledge of fungal metabolism efforts are being made to inhibit specific enzymes involved in different biochemical pathways for the development of antifungal drugs. Chitin synthase is one such promising target as it is absent in plants and mammals. Nikkomycin Z, a chitin synthase inhibitor is under clinical development. Chitin synthesis in fungi, chitin synthase as a target for antifungal agent development, different chitin synthase inhibitors isolated from natural sources, randomly synthesized and modified from nikkomycin and polyoxin are discussed in this review.
Keywords: Antifungal agents; Chitin synthase; Chitin synthase inhibitors; Nikkomycin; Peptidyl nucleoside antibiotics; Polyoxin

Chitinolytic enzymes: an appraisal as a product of commercial potential - Chavan, S. B.; Deshpande, Mukund V. (Biotechnology Progress, 2013)
Chitin, its deacetylated form, chitosan and chitinolytic enzymes viz. endo-chitinase, N-acetylglucosaminidase, chitosanase, chitin deacetylase (CDA) are gaining importance for their biotechnological applications. Presently, chitin degrading enzymes constitute high-cost low-volume products in human health care and associated research. Indeed chitinases and CDA-chitosanase complex possesss tremendous potential in agriculture to control plant pathogenic fungi and insects. The success in exploring chitinases especially for agriculture, i.e. as a high-volume low-cost product, depends on the availability of highly active preparations with a reasonable cost. Therefore, a reconsideration in terms of understanding the roles of chitinolytic enzymes in applications, e.g. host-pathogen interaction for biocontrol, different mechanisms of chitin degradation, and identification of new enzymes with varying specificities, may make them more useful in a variety of commercial processes in the near future. The possible issues and challenges encountered in the translation of proof of concept into a commercial product will be appraised in this review. (c) 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:833-846, 2013
Keywords: chitin deacetylase; chitinase; chitosanase; high-cost low-volume product; high-volume low-cost product

C. Siva Raman (1923-2014) - Deshpande, Mukund V. (Current Science, 2015)

Clerodane type diterpene as a novel antifungal agent from polyalthia longifolia var. pendula - Bhattacharya, Asish K.; Chand, Hemender R.; John, Jyothis; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2015)
Bioactivity-guided chemical examination of methanolic extract of leaves of Polyalthia longifolia var. pendula led to the isolation of the active constituent, a diterpene 1 which was identified as 16α-hydroxycleroda-3,13(14)Z-dien-15,16-olide on the basis of its spectral data. Among the tested strains, diterpene 1 was found to exhibit antifungal activities having MIC90 values of 50.3, 100.6 and 201.2 μM against Candida albicans NCIM3557, Cryptococcus neoformans NCIM3542 (human pathogens) and Neurospora crassa NCIM870 (saprophyte), respectively. Initial, structure–activity-relationship (SAR) data generated by synthesizing some derivatives revealed that the double bond between C3–C4 and the free hydroxyl group at C16 are crucial for the antifungal activity of the diterpene 1. The mode of action of 1 in C. albicans is due to compromised cell membrane permeability and also probably due to disruption of cell wall structures. The red blood cell haemolysis of all the compounds (1–4) did not show any significant haemolysis and was found to be less than 15% for all the compounds when tested at highest concentration, i.e. 1200 μM. Interestingly, all the tested compounds inhibited Y–H transition in dimorphic C. albicans NCIM3557 at much lower concentration than their MIC90 values. Determination of ROS generation by diterpene 1 using DCFH-DA and DHR123 (dihydrorhodamine) staining of C. albicans NCIM3557 indicated production of intracellular ROS as a mechanism of antifungal activity.
Keywords: Diterpene; Polyalthia longifolia; Isolation; Flash chromatography; Natural products; Antifungal activity

Cu-catalyzed sequential C-N bond formations: expeditious synthesis of tetracyclic indoloindol-3-ones - Kulkarni, Anand M.; Srinivas, Kolluru; Deshpande, Mukund V.; Ramana, Chepuri V. (Organic Chemistry Frontiers, 2016)
The tetracyclic indoloindol-3-one core has been forged from easily accessible 2,2'-bis-bromochalcones employing a reaction cascade comprising Cu-catalyzed SNAr with azide; nitrene C-H insertion and intramolecular Ullmann reaction with all three C-N bond formations in one-go.